DIFFUSION OF CIVIC ENGAGEMENT LITERATURE WEBSITE INNOVATION FOR SMART AND PARTICIPATORY VILLAGE COMMUNITIES - Abdinur Batubara (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2022)
DIFFUSION OF CIVIC ENGAGEMENT LITERATURE WEBSITE INNOVATION FOR SMART AND PARTICIPATORY VILLAGE COMMUNITIES ABTRACTThis research was conducted to develop a digital-based literacy innovation in an effort to form participatory village citizen engagement literacy. The method used is a qualitative method and a realist ethnographic research design. The population is the people of Tumpatan village, Beringin sub-district, Deli Serdang regency and the sample is people aged 17-36 years. The data analysis used is the Miles and Hubermann model data analysis. Based on the research results obtained, it shows that the existence of a civic engagement literacy website developed by the research team has a positive impact on the Tumpatan village community so that their daily activities in the village support the realization of a participatory village. So that the website project is empowered by the village community to explore their various activities in the fields of politics, education, social, religion, art, etc.Keywords: Civic Engagement, Educational innovation, and citizen participation.